Occurrence of alien invasive plant species in vegetation syntaxa of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
A presenceof 40 alien invasive plant species within plant communities of 21 class of vegetation of Ukraine was found together with syntaxonomical preferences of invasive species. Species–transformers of natural and seminatural plant communities are listed. A place and role of differentvegetation classes with different sensitivity to invasions are defined in the whole invasive process.
Keywords: phytoinvasions, alien invasive plants, syntaxa of vegetation of Ukraine, plant communities.